Attracting Diverse Students to Field Experiences Requires Adequate Pay, Flexibility, and Inclusion. (14th April 2021) - Jensen, Alex J; Bombaci, Sara P; Gigliotti, Laura C; Harris, Stephen N; Marneweck, Courtney J; Muthersbaugh, Mike S; Newman, Blaise A; Rodriguez, Shari L; Saldo, Elizabeth A; Shute, Kyle E; Titus, Keifer L; Williams, Amanda L; et al.
Abstract: Access to field experiences can increase participation of diverse groups in the environmental and natural resources (ENR) workforce. Despite a growing interest among the ENR community to attract and retain diverse students, minimal data exist on what factors undergraduate students prioritize when applying for field experiences. Using a nationwide survey of US undergraduate ENR students, we show that attracting most students to field experiences—especially racial or ethnic minority students—will require pay above minimum wage. However, the concurrent landscape of pay in ENR fell short of meeting many students' pay needs. Aside from pay, ENR students valued training in technical field skills and analytical or research skills, working with their desired study species or taxa, and working near school or family. Additional barriers beyond limited pay included incompatible schedules and noninclusive work environments. Our findings provide important insights for attracting a diverse workforce to this critical stage in career advancement for students in ENR.